Improving the twilight model for polar cap absorption nowcasts. Issue 11 (5th November 2016) - Rogers, N. C.; Kero, A.; Honary, F.; Verronen, P. T.; Warrington, E. M.; Danskin, D. W.
Abstract: During solar proton events (SPE), energetic protons ionize the polar mesosphere causing HF radio wave attenuation, more strongly on the dayside where the effective recombination coefficient, α eff, is low. Polar cap absorption models predict the 30 MHz cosmic noise absorption, A, measured by riometers, based on real‐time measurements of the integrated proton flux‐energy spectrum, J . However, empirical models in common use cannot account for regional and day‐to‐day variations in the daytime and nighttime profiles of α eff ( z ) or the related sensitivity parameter, m = A / J . Large prediction errors occur during twilight when m changes rapidly, and due to errors locating the rigidity cutoff latitude. Modeling the twilight change in m as a linear or Gauss error‐function transition over a range of solar‐zenith angles ( χ l  <  χ  <  χ u ) provides a better fit to measurements than selecting day or night α eff profiles based on the Earth‐shadow height. Optimal model parameters were determined for several polar cap riometers for large SPEs in 1998–2005. The optimal χ l parameter was found to be most variable, with smaller values (as low as 60°) postsunrise compared with presunset and with positive correlation between riometers over a wide area. Day and night values of m exhibited higher correlation for closely spaced riometers. A nowcast simulation is presented in which rigidity boundary latitude and twilight model parameters are optimized by assimilating age‐weighted measurements from 25 riometers. The technique reduces model bias, and root‐mean‐square errors are reduced by up to 30% compared with a model employing no riometer data assimilation. Plain Language Summary: The active sun occasionally ejects streams of very high‐energy protons towards the Earth. These are guided by the geomagnetic field into the polar regions where they ionise the upper atmosphere (ionosphere). The ionised plasma strongly absorbs shortwave radio signals used for long‐distance communications and this can persist for several days. This study shows how real‐time measurements from multiple ground sensors (as well as satellites) are needed to improve the accuracy of radio absorption nowcasts. In particular, it examines and models the rapid changes in ionospheric absorption at twilight, the rate of which can vary greatly, both regionally and from day to day. Key Points: Parameters of an empirical PCA model are optimized by using riometers A linear twilight transition model provides a better fit than "Earth‐shadow" methods Postsunrise delays in absorption increases are large and highly variable